Delta-crystallin genes become hypomethylated in postmitotic lens cells during chicken development. - Sullivan, C H (1987)
Although it has been argued that the loss of 5-methylcytosine from specific sites in DNA plays an important role in activation of specific genes, the mechanism of hypomethylation is not well understood. One model links the process to DNA replication, proposing that it occurs by not remethylating cytosine on newly synthesized DNA. An alternative model argues that hypomethylation results from excision of part or all of the 5-methylcytosine. We were able to test whether hypomethylation can occur without replication by analysis of methylation changes in the delta-crystallin genes of the chicken lens. During embryonic development a large fraction of cells in the lens stops dividing as part of the differentiation process. Shortly after this stage, the delta-crystallin genes in samples of the whole lens become hypomethylated, suggesting the possibility that this process might be occurring in the subset of cells that is no longer dividing. We found that hypomethylation of these genes does occur in postmitotic lens cells, a result that implicates an excision mechanism in this tissue.